IS THE ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL ACCOUNTING, AGENCY COST IMPACT ON COMPANY PERFORMANCE? (CASE STUDY OF REGIONAL WATER COMPANIES IN INDONESIA) - Hendra Setiawan (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
Companies that want to continue, exist and thrive in this day must make an increase in company performance. The performance referred to here is not just performance according to the company wishes but in accordance with customer needs. Factors that influence the company's current performance are environmental factors and agency cost. This study will analyze the impact of environmental performance, environmental accounting and agency cost on company performance. The target population of this research is the local water company (PDAM) of 34 PDAMs out of 368 PDAMs which were evaluated based on PDAM performance audit reports up to 2016 conducted by BPKP and financial audits by the Public Accountant Office (KAP). Data collection techniques are primary data through questionnaires that are shared with PDAM stakeholders and secondary data on PDAM performance audit reports. The results showed that environmental performance had a significant negative impact on PDAM company performance because of its impact value - 0.334 and the t-statistic was 3.589. Meanwhile, environmental accounting and agency cost have a significant positive impact on the performance of PDAM where the impact values are 0.4692 and 0.3816 and their t-statistics values are 7.3769 and 3.522, respectively. The PDAM must pay attention to its environmental performance impactively and efficiently by always paying attention to environmental accounting and agency costs.